(untitled) (Indian Journal of Animal Production and Management, 2024)
Throughout their productive lives, dairy cows experience numerous transitional phases that are associated with increased metabolic and infectious disease susceptibility. Redox equilibrium is crucial for guaranteeing a smooth transition. Nonetheless, oxidative stress (OS), a consequence of redox imbalance, has been linked to a higher disease risk in these animals. The periparturient and neonatal phases of the productive cycle of dairy cows are times of increased OS and disease susceptibility. This article reviews the relationship of redox status and OS with diseases of cows and calves, and how supplementation with various antioxidants can be used to prevent OS in these animals.